2022
DOI: 10.1039/d2cc00377e
|View full text |Cite
|
Sign up to set email alerts
|

Mn2(CO)10 and UV light: a promising combination for regioselective alkene hydrosilylation at low temperature

Abstract: The low temperature regioselective hydrosilylation of various alkenes with (1,1,1,3,5,5,5-heptamethyltrisiloxane) MDHM is described using Mn2(CO)10 under UV irradiation with Mn loadings as low as 1 mol%, in the absence of additives and with excellent selectivity and yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
(29 reference statements)
2
10
0
1
Order By: Relevance
“…Continuing with the use of commercially available manganese precursors, a communication was recently disclosed by Thieuleux’s group about the hydrosilylation of terminal alkenes with Mn-12 (Figure ) under UV irradiation . Excellent yields toward the linear products were obtained at room temperature and in the absence of additives with the industrially relevant MD H M (1,1,1,3,5,5,5-heptamethyltrisiloxane).…”
Section: Hydrofunctionalization Of Unsaturated C–c Bondssupporting
confidence: 89%
See 1 more Smart Citation
“…Continuing with the use of commercially available manganese precursors, a communication was recently disclosed by Thieuleux’s group about the hydrosilylation of terminal alkenes with Mn-12 (Figure ) under UV irradiation . Excellent yields toward the linear products were obtained at room temperature and in the absence of additives with the industrially relevant MD H M (1,1,1,3,5,5,5-heptamethyltrisiloxane).…”
Section: Hydrofunctionalization Of Unsaturated C–c Bondssupporting
confidence: 89%
“…Continuing with the use of commercially available manganese precursors, a communication was recently disclosed by Thieuleux’s group about the hydrosilylation of terminal alkenes with Mn-12 ( Figure 4 ) under UV irradiation. 48 Excellent yields toward the linear products were obtained at room temperature and in the absence of additives with the industrially relevant MD H M (1,1,1,3,5,5,5-heptamethyltrisiloxane). The authors reported that the process was inhibited in the presence of a radical scavenger (TEMPO) but not with a Hg drop test, which is indicative of a radical pathway and a homogeneous system.…”
Section: Hydrofunctionalization Of Unsaturated C–c Bondsmentioning
confidence: 96%
“…a 1 : 2 molar ratio of alkene : silane, using two different Mn(0) and Mn( i ) complexes, namely Mn 2 (CO) 10 or MnBr(CO) 5 . 36 The reaction was set under argon in a 4 mL vial with concentrations of 0.825 M for n -octene (74 μL, 0.47 mmol) and 1.650 M for MD H M (256 μL, 0.94 mmol). Alkenes and MD H M were purified and stored under an inert atmosphere in a glovebox prior to use (see the ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…Under these experimental conditions, the anti-Markovnikov hydrosilylation products were selectively obtained in excellent yields. 36 Unfortunately, this catalytic system was found to suffer from rapid deactivation if exposed to air and required the use of quartz glassware for optimal activation under UV irradiation; thermal activation of this catalyst was unsuccessful. In order to overcome these constraints, we explored the reactivity of Mn(I) complexes as alternatives to Mn (0) complexes as Wang and co-workers had shown that MnBr (CO) 5 was able to perform anti-Markovnikov hydrosilylation of alkenes without ligands or additives.…”
Section: Introductionmentioning
confidence: 99%
“…13 In this context, the development of photoinduced manganese-catalyzed atom-transfer reactions has become a rapidly growing research area in organic synthesis because of the Earth abundance, inexpensiveness, and low toxicity of manganese. 12 g ,13 a,b ,14 In this regard, many research groups including ours have recently demonstrated that diverse radical species, such as C-, 15 Si-, 16 Ge-, 16 c and N-radicals, 17 can be easily produced from the corresponding radical precursors ( e.g. , alkyl halides, silanes, germanes, and N-halogenated sulfonamides) by an atom transfer reaction facilitated by manganese catalysis, thus enabling efficient construction of C–C and C-heteroatom bonds.…”
Section: Introductionmentioning
confidence: 91%